PENGARUH MEDIA PEMBELAJARAN POP-UP BOOK TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Mutmainnah, Yunidawati; Ratnadi, Ratnadi; Husniati, Husniati; Setiawan, Heri (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2018)
This study aims to determine the effect of Pop-Up Book Learning Media on Science Learning Outcomes of Grade V Students of SDN Gugus I Mataram StudyYear 2018/2019. This study uses an experimental method, with a type of Quasi Experimental Design type Non Equivalent Control Group Design. This research was conducted in October 2018 at SDN Gugus I Mataram. Population in this study, namely all students in Class V of SDN Gugus I Mataram. The sample was selected using purposive sampling technique, so that the sample in this study was V grade students of SDN 42 Mataram and V grade students of SDN 31 Mataram. The data collection technique used in this study was a test. The quality test of the instrument carried out is the validity test, reliability test, difficulty level test, and different power test. The data analysis methid used is the t-test with the requirements test, namely the normality test and the data homogeneity test. After the analysis was obtained the result of tcount 4,22 > ttable 2,001 at the significance level of 5%, wich means that there is the influence of Pop-Up Book leraning media on science learning outcomes of class V students of SDN Gugus I Mataram Study Year 2018/2019.